5‐Aminolevulinic acid exerts renoprotective effect via Nrf2 activation in murine rhabdomyolysis‐induced acute kidney injury. Issue 1 (16th December 2018) - Uchida, Atsushi; Kidokoro, Kengo; Sogawa, Yuji; Itano, Seiji; Nagasu, Hajime; Satoh, Minoru; Sasaki, Tamaki; Kashihara, Naoki
ABSTRACT: Aim: Acute kidney injury (AKI) is associated with chronic kidney disease, as well as high mortality, but effective treatments for AKI are still lacking. A recent study reported the prevention of renal injury, such as ischemia‐reperfusion injury, by 5‐aminolevulinic acid (ALA), which induces an antioxidant effect. The current study aimed to investigate the effect of ALA in a rhabdomyolysis‐induced mouse model of AKI created by intramuscular injection of 50% glycerol. Methods: Rhabdomyolysis‐induced AKI was induced by an intramuscular injection of glycerol (5 mL/kg body weight) into mice. Administration of ALA (30 mg/kg, by gavage) was started from 48 h before or 24 h after glycerol injection. The mice were sacrificed at 72 h after glycerol injection. The roles of nuclear factor erythroid 2‐related factor 2 (Nrf2) and heme oxygenase‐1 (HO‐1), which is one of the Nrf2‐related antioxidants, were further investigated through in vivo and in vitro methods. Results: 5‐aminolevulinic acid markedly reduced renal dysfunction and tubular damage in mice with rhabdomyolysis‐induced AKI. ALA administration decreased oxidative stress, macrophage infiltration, and inflammatory cytokines and apoptosis. The expression of Nrf2 was upregulated by ALA administration. However, administration of Zinc protoporphyrin‐9 (ZnPPIX) to inhibit HO‐1 activity did not abolish these improvements by ALA. The expression of Nrf2‐associated antioxidant factors other than HO‐1 was also increased. Conclusion: These findings indicate that ALA exerts its antioxidant activity via Nrf2‐associated antioxidant factors to provide a renoprotective effect against rhabdomyolysis‐induced AKI. Summary at a Glance: Using a mouse model of rhabdomyolysis (muscle damage)‐induced acute kidney injury, the authors present evidence that 5‐aminolevulinic acid, an amino acid and haem precursor, exerts renoprotective effects by inducing the Nrf2 transcription factor and downstream anti‐oxidant genes (heme oxygenase‐1, NQO1, and GCLM).